Protective effects of matrine on cardiomyocytes infected with coxsackievirus B₃ via modulation of the calpain-2/caspase-12 signaling pathway: Matrine protects cardiomyocytes from coxsackievirus B₃ - Sun, Yongmei; Mao, Zongtao; Liu, Junzuo; Geng, Yanan (Cellular and Molecular Biology, 2025)
Viral myocarditis (VMC) presents a substantial threat, especially for children, often leading to cardiogenic shock and fulminant myocarditis. Our study aimed to evaluate the role of calpain-2 and caspase-12, which were involved in the endoplasmic reticulum apoptosis pathway, and the influence of Matrine on these proteins during Coxsackie virus B₃ (CVB₃)-induced acute VMC mice in vitro and in vivo, shedding light on the potential cardioprotective effects. We first performed primary cultured cardiomyocytes, which were infected with CVB₃in vitro. We observed cell viability, the beating of cardiomyocytes and cytopathic effects. And we utilized Balb/c mice to establish the VMC animal model and determined viral titers, histopathological changes, and myocardial pathological scores. Furthermore, we detected CK-MB levels and myocardial cell apoptosis in vitro and in vivo. In order to further explore the possible mechanisms, the protein expression of calpain-2 (by immunohistochemistry and Western blot) and caspase-12 activity (by fluorescence assay for substrate cleavage) were detected in vitro and in vivo. Our findings indicated that, in comparison to the normal control group, the virus-infected group exhibited increased injured myocardial cells, virus titer, CK-MB levels, and apoptotic cells (P<0.05). Matrine treatment groups significantly reduced CK-MB levels, myocardial cellular damages and apoptosis in vitro and in vivo, with Matrine notably suppressing calpain-2 protein expression and Caspase-12 activity compared to the virus-infected group (P<0.05). In conclusion, our study revealed that calpain-2 and caspase-12 played roles in CVB₃-induced myocardial cell apoptosis. Matrine effectively mitigated myocardial cell injury and reduced apoptosis, thereby providing substantial protection against CVB₃infection in vitro and in vivo, which may be related to the down-regulation of calpain-2/caspase-12 signaling pathway.